Residual photosensitivity in mice lacking both rod opsin and cone photoreceptor cyclic nucleotide gated channel 3 alpha subunit. - Barnard, A; Appleford, J; Sekaran, S; Chinthapalli, K; Jenkins, A; Seeliger, M; Biel, M; Humphries, P; Douglas, R; Wenzel, A; Foster, R; Hankins, M; et al. (2004)
The mammalian retina contains three classes of photoreceptor. In addition to the rods and cones, a subset of retinal ganglion cells that express the putative sensory photopigment melanopsin are intrinsically photosensitive. Functional and anatomical studies suggest that these inner retinal photoreceptors provide light information for a number of non-image-forming light responses including photoentrainment of the circadian clock and the pupil light reflex. Here, we employ a newly developed mouse model bearing lesions of both rod and cone phototransduction cascades (Rho(-/-) Cnga3(-/-)) to further examine the function of these non-rod non-cone photoreceptors. Calcium imaging confirms the presence of inner retinal photoreceptors in Rho(-/-) Cnga3(-/-) mice. Moreover, these animals retain a pupil light reflex, photoentrainment, and light induction of the immediate early gene c-fos in the suprachiasmatic nuclei, consistent with previous findings that pupillary and circadian responses can employ inner retinal photoreceptors. Rho(-/-) Cnga3(-/-) mice also show a light-dependent increase in the number of FOS-positive cells in both the ganglion cell and (particularly) inner nuclear layers of the retina. The average number of cells affected is several times greater than the number of melanopsin-positive cells in the mouse retina, suggesting functional intercellular connections from these inner retinal photoreceptors within the retina. Finally, however, while we show that wild types exhibit an increase in heart rate upon light exposure, this response is absent in Rho(-/-) Cnga3(-/-) mice. Thus, it seems that non-rod non-cone photoreceptors can drive many, but not all, non-image-forming light responses.